Cuttings Taken from Bottom One-third Part of Populus Ciliata Plants Perform Better - Singh, R. V.; Sharma, K. C.; Kaushal, P. S. (Indian Forester, 1984)
Investigations carried out to determine the performance of cuttings taken from bottom one-third, middle one-third and top one-third portions of Populus ciliata plants showed that the cuttings taken from the bottom one-third parts of the plants performed better than those taken from the middle one-third which did better than those taken from the top one-third parts of the plants.